АДАМЗАТ ЖƏМИЙЕТИНИҢ РУЎХЫЙ-МƏДЕНИЙ ТУРМЫСЫНДА ИМПРОВИЗАЦИЯНЫҢ КЕЛИП ШЫҒЫЎ ЗƏРҮРЛИКЛЕРИ - Матимов, К.Г. (SCIENCE and SOCIETY, 2020)
The article discusses the origin of literary phenomenon improvisation in the history of ancient and Karakalpak literature, there is depicted the stages of the formation, history of its development.